PENGARUH GOOD CORPORATE GOVERNANCE, UKURAN PERUSAHAAN, DAN PROFITABILITAS TERHADAP MANAJEMEN LABA PADA BANK UMUM SYARIAH DI INDONESIA - Baehaqi, Ahmad; Mupidah, Yulia; Kamal, Mustafa (Program Studi Akuntansi, Universitas Kuningan, 2025)
This study aims to examine the effect of good corporate governance (GCG)—measured by the sharia supervisory board (SSB), board of commissioners (BoC), and institutional ownership—along with firm size and profitability on earnings management. This study employs a quantitative approach using panel data regression analysis. The data used is secondary data, consisting of annual and financial reports published by Islamic commercial banks. The study focuses on Islamic commercial banks in Indonesia from 2015 to 2022, with a total sample of 9 banks and 72 observations obtained through a purposive sampling technique. The results indicate that the SSB and BoC variables do not significantly affect earnings management. In contrast, institutional ownership, firm size, and profitability negatively affect earnings management